2012
DOI: 10.1101/sqb.2013.77.014712
|View full text |Cite
|
Sign up to set email alerts
|

Color and Scent: How Single Genes Influence Pollinator Attraction

Abstract: A major function of angiosperm flowers is the recruitment of animal pollinators that serve to transfer pollen among conspecific plants. Distinct sets of floral characteristics, called pollination syndromes, are correlated with visitation by specific groups of pollinators. Switches among pollination syndromes have occurred in many plant families. Such switches must have involved coordinated changes in multiple traits and multiple genes. Two well-studied floral traits affecting pollinator attraction are petal co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
55
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 148 publications
0
55
0
Order By: Relevance
“…Colour and scent influence the attraction of pollinators and thereby cause reproductive isolation and ultimately speciation. Speciation of P. axillaris from a P. inflata-like ancestor involved the loss of anthocyanin pigments and the gain of volatiles 4 . Thus the genes that caused the changes in these two traits are potential speciation genes.…”
Section: P Inflatamentioning
confidence: 99%
See 1 more Smart Citation
“…Colour and scent influence the attraction of pollinators and thereby cause reproductive isolation and ultimately speciation. Speciation of P. axillaris from a P. inflata-like ancestor involved the loss of anthocyanin pigments and the gain of volatiles 4 . Thus the genes that caused the changes in these two traits are potential speciation genes.…”
Section: P Inflatamentioning
confidence: 99%
“…To the scientific community, Petunia is best known for the discovery of RNAi 2,3 . This breakthrough was the culmination of decades-long research on the synthesis and regulation of the floral pigments and as a consequence anthocyanin biosynthesis remains one of the best-known pathways of secondary metabolism in any plant species 4 . Development, transposon activity, genetic self-incompatibility, and interactions with microbes, herbivores and pollinators have also been active research topics utilizing Petunia as model system.…”
mentioning
confidence: 99%
“…Petunia serves as a model for studying the regulation of AAA biosynthesis (Colquhoun et al, 2010; Maeda et al, 2011) and for the biosynthesis and regulation of AAA-derived metabolites, including volatile BPs (Colquhoun and Clark, 2011; Sheehan et al, 2012; Dudareva et al, 2013; Muhlemann et al, 2014). Recently, we showed that overproduction of the AAAs in the purple petunia (cv.…”
Section: Introductionmentioning
confidence: 99%
“…These essential compounds provide protection against UV light (flavonoids) and serve as structural components of cell walls (lignins). They also function in the defense against herbivores and pathogens, while floral pigments (anthocyanins) and scent compounds (volatile phenylpropanoids) mediate plant-pollinator interactions (Bhuiyan et al, 2009;Vanholme et al, 2010;Klahre et al, 2011;Falcone Ferreyra et al, 2012;Sheehan et al, 2012;Dudareva et al, 2013).…”
mentioning
confidence: 99%